Microeconomics principles, problems, and policies / McConnell Campbell R., Stanley L. Brue - McCornnell, Campbell, R. [et.al] (1996)
An introduction to economics and the economy, the nature and method of economics, the economizing problem, understanding individual markets, demand and supply, pure capitalism and the market system, the mixed economy, private and public sectors, the united states in the global economy; microeconomics of product markets, demand and supply, elasticies and appliciatons, consumer behavior and utility maximization, the cost of production, price and output determination, pure comtition, price and output determination, pure monopoly, price and output determination, monopolistic comtetition, price and output determination, oligopoly; microeconomics of resource markets, production and the demand for resources, the priceing and employment of resources, wage determination, the princing and employment of resources, rent, inte3rest, and profits; Government and current economics problems, government and market failure, public goods, the environment, and information, public choice theory and taxation, antiturust, regulation, and industrial policy, agriculture, economics and policy, income inequality and poverty, the economics of health care, labor marketi issues, unionista, discrimination, and immigration, international economics and the world economy